Telehealth on heart failure: results of the Recap project. (September 2015) - Varon, Carolina; Alao, Morenikeji; Minter, Jan; Stapleton, Michelle; Thomson, Stuart; Jaecques, Siegfried; Rocca, Hans-Peter BL; Huffel, Sabine V
Telehealth has become a very important tool that allows the monitoring of heart failure patients in a home environment. However, little is known about the effect that such monitoring systems have on patients' compliance, evolution and self-care behaviour. In particular, the effect that the selected user interface has on these factors is unknown. This study aims to investigate this, and to determine some practicalities that must be considered when designing and implementing a telehealth programme for heart failure. To achieve this, daily measurements of blood pressure, pulse, SpO2 and weight were collected from 534 patients suffering from heart failure. In addition, they were asked to fill in the European heart failure self-care behaviour scale questionnaire and the EQ-5D quality of life questionnaire, before and after the monitoring period. Two telehealth systems were used, the Motiva platform provided by Philips and the standalone unit provided by Docobo, the Doc@Home system. Significant differences were found between both systems concerning the compliance and adherence of patients. Moreover, a general, positive effect of telehealth was identified due to the fact that patients showed an increased self-awareness when managing their condition. These findings are supported by behavioural changes and a better understanding of heart failure from the patients' perspective.